Teacher Professional Development: Perspectives from a Research Experience with Teachers - Carolina Aparicio-Molina; Felipe Sepúlveda-López (Universidad Nacional, Costa Rica, 2023)
Objective. To analyze the scope of realization of professional learning communities with teachers and management teams who implemented that intervention during two years in a high school in the south of Chile. Methodology. In this applied research, teachers participated in phases of diagnosis of training needs for professional development. Based on this, a proposal of work sessions theoretically and methodologically linked to the professional learning communities was structured. The proposal was designed and implemented together with the school's management team. After the implementation, the study followed with qualitative interviews and focal groups about the experience conducted with 17 participants; these instances were analyzed by thematic analysis following the phenomenological approach. Analysis of Results. The analyses allowed the emergence of three elements related to professional learning and agency capacity. It was especially evident that teachers recognized their capacity to take charge of their professional learning by considering work routines, focusing on learning as a positive factor among teachers and being important in all phases of a collaborative work design. Conclusions. The findings show that, although specific stimuli, spaces, and moments are required to encourage teachers' work, it is possible to improve based on their own capacities, i.e., within each establishment, there is the possibility of achieving learning for all. This call is addressed to pedagogical leaders, who can modify their roles and adapt to professionals recognized as agents of change.